1986
DOI: 10.1007/bf00269638
|View full text |Cite
|
Sign up to set email alerts
|

Flavor formation in tissue cultures of garlic (Allium sativum L.)

Abstract: Differentiated and undifferentiated cultures of garlic (Allium sativum L.) were analyzed for the study of flavor formation in cultures. Attempts were made to correlate alliin content with free and bound amino acid contents and with enzymes like phenylanine ammonialyase (E.C. 4.1.1.5) and alliin-lyase (E.C.4.4.1.4) which play important roles in formation of the flavor percursor alliin.It was observed that in differentiating cultures showing shoot formation, there is an increase in alliin content as well as in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In other studies on garlic, Brodnitz et al (1971) reported that diallyl thiosulfinate is a major odor compound and Nishimura et al (1971) claimed that methyl ally1 disulfide, diallyl disulfide, and methyl ally1 trisulfide are the major odor compounds. These determinations, however, were done under in vitro conditions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other studies on garlic, Brodnitz et al (1971) reported that diallyl thiosulfinate is a major odor compound and Nishimura et al (1971) claimed that methyl ally1 disulfide, diallyl disulfide, and methyl ally1 trisulfide are the major odor compounds. These determinations, however, were done under in vitro conditions.…”
Section: Introductionmentioning
confidence: 96%
“…THE IDENTITY OF odor compounds in human mouth air after garlic ingestion have yet to be established, even though a number of volatile compounds of garlic have been determined (Akashi et al, 1975;Freeman, 1975;Malpathak and David, 1986). In other studies on garlic, Brodnitz et al (1971) reported that diallyl thiosulfinate is a major odor compound and Nishimura et al (1971) claimed that methyl ally1 disulfide, diallyl disulfide, and methyl ally1 trisulfide are the major odor compounds. These determinations, however, were done under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Certain flavours consist of one or a few compounds only, namely, 2isobutyl-thiozole (tomato), methyl ethyl cinnamates (strawberry), methyl anthranilate (grape), benzaldehyde (cherry), menthol (mint) and safranal (saffron) (Sujata et a1 1990). Some flavours such as celery (A1 Abta et a1 1979), onion (Turnbull et a1 I98 l), garlic (Malpathak and David 1986) need a certain level of differentiation in callus or cell suspension cultures for the biosynthesis of flavour compounds in tissue cultures. In the case of rice no such differentiation was found in the cells for flavour production.…”
Section: Resultsmentioning
confidence: 99%
“…These are compounds mostly of pharmaceutical interest. Flavour synthesis in in-vitro plant cell cultures has been demonstrated in only a few instances, such as onion, garlic, celery, chilli pepper and citrus (Bricout and Paupardin 1974;Al-Abta et a1 1979;Selby et a1 1980;Lindsey and Yeoman 1984;Malpathak and David 1986). Information on tissue cultures of fruits is very I05 J Sci.…”
Section: Introductionmentioning
confidence: 99%